We have to find the derivative of : y = 3 - (3/(5x))

y = 3 - (3/(5x))

y' = [3 - (3/(5x))]'

=> y' = [3]' - [(3/5)*(1/x)]'

The derivative of a constant term is 0 and that of x^n is n*x^(n-1)

=> y' = 0 - (3/5)(-1)*x^(-1-1)

=> y' = (3/5)/x^2

=> y' = 3/(5*x^2)

**The derivative of 3 - (3/(5x)) is 3/(5*x^2)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now